Catalytic macroporous biohydrogels made of ferritin-encapsulated gold nanoparticles - Kumari, Sushma; Haring, Marleen; Sen Gupta, Sayam; Diaz, David Diaz (Chempluschem, 2017)
Reported is a modular approach for the incorporation and stabilization of gold nanoparticles inside a three-dimensional macroporous hydrogel made of ferritin. The strategy, which involves the dynamic templating of surfactant H-1 domains, demineralization, and remineralization helps to overcome aggregation and degradation issues usually associated with bare-metal-based nanocatalysts. The catalytic activity of the so-synthesized bionanocomposite hydrogel was demonstrated in both nitroaldol (Henry) and nitroreduction model reactions in aqueous solution at room temperature. An interesting synergistic effect between basic residues of the protein and the gold nanoparticles was found in the nitroaldol reaction when carried out in water in the presence of a phase-transfer catalyst. Furthermore, the reduction of 4-nitrophenol and 4-nitroaniline catalyzed by the nanocomposite scaffold in the presence of NaBH4 proceeded significantly faster than that using other known Au- and Ag-based catalysts under similar conditions.